MOOCs Continuance Intention in Malaysia: The Moderating Role of Internet Self-efficacy - Mohd Kamarul Irwan Abdul Rahim; Mawaddah Mohamad (International Journal of Supply Chain Management, 2018)
Previous researches have validated that students intention to continue use MOOCs was mainly determined by Usefulness and Enjoyment. This paper takes a different approach from previous studies and postulates that relationship between Usefulness and Enjoyment on MOOCs Continuance Intention are moderated by Internet Self-efficacy. Partial Least Square Path Modelling (PLS-PM) approach has been employed to analyse the data collected. Using online survey data from 251 students registered with Malaysia MOOCs program, the results revealed that Internet Self-efficacy moderates the relationship between Enjoyment and MOOCs Continuance Intention. However, the moderating effect of Internet Self-efficacy showed insignificant result on the path between Usefulness and MOOCs Continuance Intention.